The Reality of Parents' Monitoring and Guidance on their Children Use of the Social Networks in Ar'ar City - Alenezy, Abdulaziz (Dirasat: Human and Social Sciences, 2021)
The study aims at investigating the reality of parents' monitoring and guidance on their children use of the social networks in Ar'ar city in the Kingdom of Saudi Arabia. The population of study consisted of all parents who have children in Ar'ar city in KSA in 1440AH. The study sample consisted of (248) parents; they were distributed on the variables (gender, mother's job, qualifications and number of children). The sample was chosen by snowball method. The study followed the descriptive analytical approach and used questionnaire developed for the purposes of study. The results showed that the sample valuation of the degree of the families' monitoring on their children use of the social networks was moderate, while the families' guidance was high. In both the monitoring and guidance domains, the results showed that there were differences in the parent's valuations in favor of mothers, and in the monitoring domain in favor of working mothers. There were no statically significant differences due to the qualification, while the results showed that the guidance decreases in the families with more than (6) children. The study recommended the necessity of holding educational sessions and workshops by the concerned authorities for parents on the effects of social networks on children, and how to deal with them in a safe way.